2022
DOI: 10.3390/ijerph19137840
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Ecological Factors and Well-Being among Self-Employed in Europe during the COVID-19 Pandemic

Abstract: Background: The self-employed are at increased risk of negative well-being outcomes when facing adversity such as the COVID-19 pandemic. Studies that examine socio-ecological factors that may protect their well-being are warranted. Methods: Data were drawn from a cross-sectional survey of European self-employed people (n = 1665). The WHO-5 Well-being Index was used to examine the impact on well-being of factors at four socio-ecological levels. Independent sample t-tests, Pearson correlations and linear regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The risk factors may come from other environmental factors (16) including a clean and healthy lifestyle as well as the nutritional intake that has been carried out by pulmonary TB patients (17). The increasing r e s i d e n t i a l d e n s i t y h a d a s i g n i fi c a n t relationship with the potential for pulmonary TB transmission (18), (13). The current study found that pulmonary TB patients mostly live in houses with humidity that have met the requirements for a healthy home (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk factors may come from other environmental factors (16) including a clean and healthy lifestyle as well as the nutritional intake that has been carried out by pulmonary TB patients (17). The increasing r e s i d e n t i a l d e n s i t y h a d a s i g n i fi c a n t relationship with the potential for pulmonary TB transmission (18), (13). The current study found that pulmonary TB patients mostly live in houses with humidity that have met the requirements for a healthy home (19).…”
Section: Discussionmentioning
confidence: 99%
“…In order to figure out whether the environmental condition is one of the factors which influence the transmission of pulmonary TB (12), this study focuses to examine the environmental conditions including residential density (13), house ventilation, room humidity, and house lighting (10). The purpose of the c u r r e n t s t u d y w a s t o fi g u r e o u t t h e environmental factor determining the incidents of pulmonary TB in Surabaya City.…”
mentioning
confidence: 99%